Tumor endothelial cells with high aldehyde dehydrogenase activity show drug resistance. Issue 11 (17th September 2017) - Hida, Kyoko; Maishi, Nako; Akiyama, Kosuke; Ohmura‐Kakutani, Hitomi; Torii, Chisaho; Ohga, Noritaka; Osawa, Takahiro; Kikuchi, Hiroshi; Morimoto, Hirofumi; Morimoto, Masahiro; Shindoh, Masanobu; Shinohara, Nobuo; et al.
Abstract : Tumor blood vessels play an important role in tumor progression and metastasis. We previously reported that tumor endothelial cells (TEC) exhibit several altered phenotypes compared with normal endothelial cells (NEC). For example, TEC have chromosomal abnormalities and are resistant to several anticancer drugs. Furthermore, TEC contain stem cell‐like populations with high aldehyde dehydrogenase (ALDH) activity (ALDH high TEC). ALDH high TEC have proangiogenic properties compared with ALDH low TEC. However, the association between ALDH high TEC and drug resistance remains unclear. In the present study, we found that ALDH mRNA expression and activity were higher in both human and mouse TEC than in NEC. Human NEC:human microvascular endothelial cells (HMVEC) were treated with tumor‐conditioned medium (tumor CM). The ALDH high population increased along with upregulation of stem‐related genes such as multidrug resistance 1, CD90, ALP, and Oct‐4. Tumor CM also induced sphere‐forming ability in HMVEC. Platelet‐derived growth factor (PDGF)‐A in tumor CM was shown to induce ALDH expression in HMVEC. Finally, ALDH high TEC were resistant to fluorouracil (5‐FU) in vitro and in vivo . ALDH high TEC showed a higher grade of aneuploidy compared with that in ALDH low TEC. These results suggested that tumor‐secreting factor increases ALDH high TEC populations that are resistant to 5‐FU. Therefore, ALDH high TEC in tumor blood vessels might be an important target to overcome or prevent drug resistance. Abstract : There are TEC with high ALDH activity. ALDH expression was induced by tumor‐derived factor.TEC with high ALDH activity show drug resistance.